Mengulas Peran Imajinasi dalam Pencarian Kebenaran dan Keyakinan Perspektif Immanuel Kant dan Cornelius Castoriadis - Dinar Indah Guniarti; Komarudin Sassi (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2024)
This research aims to examine the extent to which imagination plays a role in the search for truth and the formation of human beliefs, with a focus on the perspective of Immanuel Kant and Cornelius Castoriadis. Kant, within the framework of his critical philosophy, underscores the central role of imagination in shaping our aesthetic, moral and knowledge experiences. Imagination, for him, is the power of synthesis that connects empirical data with pure concepts of reason. Meanwhile, Castoriadis sees imagination as a creative force that underlies the formation of society and individual identity. Imagination, in Castoriadis's perspective, is the source of all social institutions, values and norms. This study will carry out an in-depth comparison between Kant's and Castoriadis' views regarding the role of imagination. It is hoped that this comparative analysis will reveal the points of contact and differences between the two philosophers, as well as provide a more nuanced understanding of the dynamics of imagination in human life. This research uses a conceptual analysis approach to analyze and compare the ideas of the two philosophers. In this way, it is hoped that it can contribute to philosophical studies regarding epistemology, especially regarding the formation of knowledge and reality. Apart from that, this study is also relevant to the study of social philosophy, because imagination has a central role in the formation of society and collective identity.